1998
DOI: 10.1001/archderm.134.8.995
|View full text |Cite
|
Sign up to set email alerts
|

Is Common Neonatal Cephalic Pustulosis (Neonatal Acne) Triggered by Malassezia sympodialis?

Abstract: Background: A type of neonatal cephalic pustulosis that is clinically similar to classic neonatal acne recently has been linked to Malassezia furfur infection. To correlate the mycological and clinical findings in neonates with cephalic pustulosis, we carried out a prospective case-control study in a neonatal unit from February to April 1997 using new techniques for classifying Malassezia species.Observations: Nineteen patients with cephalic pustulosis and 19 controls younger than 45 days were studied among 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…Malassezia has been associated with a wide range of other superficial diseases, including acne vulgaris (21,206), dacryocystitis (474), seborrhoeic blepharitis (440), neonatal pustulosis (19,309,336,350), confluent and reticulated papillomatosis (136,215,223,236,366,481,482), onychomycosis (97, 400), nodular hair infection (262), and psoriasis (120,124,140,373,374,376). In many of these reports, the isolation of Malassezia was taken as proof of its involvement in the disease, an assumption that may not be correct due to its presence on the skin as a commensal.…”
Section: Other Superficial Diseasesmentioning
confidence: 99%
“…Malassezia has been associated with a wide range of other superficial diseases, including acne vulgaris (21,206), dacryocystitis (474), seborrhoeic blepharitis (440), neonatal pustulosis (19,309,336,350), confluent and reticulated papillomatosis (136,215,223,236,366,481,482), onychomycosis (97, 400), nodular hair infection (262), and psoriasis (120,124,140,373,374,376). In many of these reports, the isolation of Malassezia was taken as proof of its involvement in the disease, an assumption that may not be correct due to its presence on the skin as a commensal.…”
Section: Other Superficial Diseasesmentioning
confidence: 99%
“…Our patients' rash often required treatment with antibiotics and was more chronic than NCP. 29 It is possible that the newborn rash of HIES represents EPF, ETN, or NCP that has become infected, leading to a progressive course that requires antibiotics. It is also possible that the newborn rash of HIES is an aberrant response to S aureus with eosinophils rather than neutrophils because of an underlying immune defect.…”
Section: Newborn Rashmentioning
confidence: 99%
“…It is thought to be due to the development of lipophilic yeasts in predisposed newborns who have increased sebum production. It has been demonstrated that Malassezia species, in particular, have a role in the etiopathogenesis of NCP [10,11]. At birth, Malassezia colonization develops, depending on environmental factors, maternal contact, and the characteristics of newborn skin; it gradually increases within the first months of extrauterine life.…”
Section: Neonatal Cephalic Pustulosismentioning
confidence: 99%
“…These fungi, which are found in the normal skin flora of infants, likely lead to follicular occlusion in predisposed infants who have increased sebum production. This, in turn, causes acneiform eruptions [8,10,12,13]. However, the presence of negative mycological data in some NCP cases and the absence of NCP development in some culture-positive newborns lead us to believe that different factors also have an effect [1,5].…”
Section: Neonatal Cephalic Pustulosismentioning
confidence: 99%